Characterization of the CAZy Repertoire from the Marine-Derived Fungus Stemphylium lucomagnoense in Relation to Saline Conditions - Wissal Ben Ali; David Navarro; Abhishek Kumar; Elodie Drula; Annick Turbé-Doan; Lydie Oliveira Correia; Stéphanie Baumberger; Emmanuel Bertrand; Craig B. Faulds; Bernard Henrissat; Giuliano Sciara; Tahar Mechichi; et al. (Marine Drugs, 2020)
Even if the ocean represents a large part of Earth’s surface, only a few studies describe marine-derived fungi compared to their terrestrial homologues. In this ecosystem, marine-derived fungi have had to adapt to the salinity and to the plant biomass composition. This articles studies the growth of five marine isolates and the tuning of lignocellulolytic activities under different conditions, including the salinity. A de novo transcriptome sequencing and assembly were used in combination with a proteomic approach to characterize the Carbohydrate Active Enzymes (CAZy) repertoire of one of these strains. Following these approaches, Stemphylium lucomagnoense was selected for its adapted growth on xylan in saline conditions, its high xylanase activity, and its improved laccase activities in seagrass-containing cultures with salt. De novo transcriptome sequencing and assembly indicated the presence of 51 putative lignocellulolytic enzymes. Its secretome composition was studied in detail when the fungus was grown on either a terrestrial or a marine substrate, under saline and non-saline conditions. Proteomic analysis of the four S. lucomagnoense secretomes revealed a minimal suite of extracellular enzymes for plant biomass degradation and highlighted potential enzyme targets to be further studied for their adaptation to salts and for potential biotechnological applications.